George Cruikshank and his bottle - Paisana, Joanne (2004)
In tribute to Prof. Hélio Osvaldo Alves, this chapter examines George Cruikshank's teetotal convictions through his painting 'The Worship of Bacchus' (1860-62) and his highly popular illustrated series 'The Bottle' (1847).